Broken ground ebook - McDermid, Val (Karen Pirie, 2020)
A woman digs up a buried treasure—and a buried body—in the Scottish Highlands: “There are few other crime writers in the same league.”—Maureen Corrigan, The Washington Post Six feet under in a Highland peat bog lies Alice Somerville’s inheritance, buried by her grandfather at the end of World War II. But when Alice finally uncovers it, she finds an unwanted surprise—a body with a bullet hole between the eyes. Meanwhile, DCI Karen Pirie is dealing not only with this cold case but with a domestic violence case, and as as she gets closer to the truth, it becomes clear that not everyone shares her desire for justice. Or even the idea of what justice is. An engrossing, twisty thriller,  Broken Ground  is an outstanding entry in this Diamond Dagger-winning author’s “superior series” ( The New York Times Book Review ).   “As always, McDermid’s story lines are as richly layered as her protagonist.”— Publishers Weekly   “One of the best things about this series is the details of Karen's working life, the obstacles as well as the satisfactions, and the small pleasures of her off hours.”— Kirkus Reviews